2014
DOI: 10.1253/circj.cj-13-1187
|View full text |Cite
|
Sign up to set email alerts
|

Production of Reactive Oxygen Species in the Diabetic Heart

Abstract: 300TESHIMA Y et al. Circulation JournalOfficial Journal of the Japanese Circulation Society http://www. j-circ.or.jp iabetes mellitus (DM) is an independent risk factor of heart failure. The Framingham Heart Study reported that the frequency of heart failure is 2-fold higher in male diabetics and 5-fold higher in female diabetics than in age-matched control subjects. 1 An increase in reactive oxygen species (ROS) has been regarded as a dominant mechanism of cardiac dysfunction in patients with DM. 2-4 ROS are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
74
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(74 citation statements)
references
References 97 publications
(69 reference statements)
0
74
0
Order By: Relevance
“…Accumulating evidence suggests that mitochondria and NADPH oxidase important sources of ROS production in the diabetic heart (34)(35)(36), where the crosstalk between mitochondria and NADPH oxidase is important and represents a feed-forward vicious cycle of ROS production (37,38). It is important to elucidate the cellular mechanisms of ROS increase in the diabetic heart.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that mitochondria and NADPH oxidase important sources of ROS production in the diabetic heart (34)(35)(36), where the crosstalk between mitochondria and NADPH oxidase is important and represents a feed-forward vicious cycle of ROS production (37,38). It is important to elucidate the cellular mechanisms of ROS increase in the diabetic heart.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of glyceraldehyde 3-phosphate can increase the synthesis of diacylglycerol that is an activator of protein kinase C (PKC). PKC activation is known to be involved in elevating the content of TGF- β -1, endothelin-1, NF- κ B, and vascular endothelial growth factor [22, 143, 144] and is also known to induce ROS production by NADPH oxidase that catalyzes one electron reduction of molecular oxygen to form superoxide [145147]. Mechanistically, it has been established that PKC activates NADPH oxidase by phosphorylating the p47 phox subunit, triggering the translocation of this subunit from cytosol to membrane whereby it assembles with other components to form an active NADPH oxidase that is capable of making superoxide from oxygen [148, 149].…”
Section: The Branching-off Pathways and Oxidative Stressmentioning
confidence: 99%
“…These findings agreed those previous studies and indicated that these two organs were vulnerable to diabetes. NADPH oxidase complex plays an important role in diabetes-induced ROS generation [21,22]. We examined the influence of aqueous extract of H. cordata leaves upon the expression of p47 phox and gp91 phox , NADPH oxidase cytosolic and membrane components, and our data revealed that this extract effectively downregulated cardiac and renal protein expression of p47 phox , which in turn led to lower ROS …”
Section: Discussionmentioning
confidence: 94%